Barrier height control in metal/silicon contacts with atomically thin MoS2 and WS2 interfacial layers. (16th August 2018) - Nam, Seung-Geol; Cho, Yeonchoo; Lee, Min-Hyun; Shin, Keun Wook; Kim, Changhyun; Yang, Kiyeon; Jeong, Myoungho; Shin, Hyeon-Jin; Park, Seongjun
Abstract: As complementary metal-oxide-semiconductor technology nodes are scaled down, lowering the contact resistance has become a critical problem for continued scaling. In this study, we suggested the reduction method of the Schottky barrier height, one of the main causes of contact resistance, by insertion of atomically thin two-dimensional (2D) materials between the metal and Si interface. Also, we found that the inserted 2D materials could modulate the work function of the metal and mitigate the Fermi level pinning, leading to reduced barrier height and, hence, reduced contact resistance of the metal–semiconductor junction. With the insertion of MoS2 and WS2 materials a two-layer thick, we achieved 160 meV reductions in the Schottky barrier height and increased the current density by 14 times for titanium contact to the n-type silicon. Finally, we suggested a modified band diagram of Ti/n-Si contacts with the 2D interfacial layer. Our results showed that employing 2D materials can be an alternative route for overcoming the contact resistance challenges in modern transistors.